The mediating effect of psychological ownership on human resources management bundle and job satisfaction ownership - Yolanda Masnita; Pipie Puspitasari; Renny Risqiani (Journal of Economics, Business, and Accountancy Ventura, 2019)
AMO (ability, motivation, and opportunity) is one of the measurements used in Human Resource Management and for explaining the Innovation of Human Resources Management Bundle (IHRMB) that can affect job satisfaction and welfare. It explained that if a skilled, motivated employees will have the opportunity to contribute by using their knowledge and competencies. They will feel having a maximum job satisfaction. This study examine the role of psychological ownership for organizations (PO-O) in mediating the effect of IHRMB on the Job Satisfaction of bank employees (bankers). With a purposive sampling of inclusion criteria, a questionnaire was given to 100 bankers, testing the hypothesis with SEM. The results show that IHRMB affects PO-O and Job Satisfaction. The IHRMB is prepared at the end of the year to be able to have the right strategy for employees the following year, in addition to being a connector between the owner of the company to employees through a collection of innovations summarized in the IHRMB as well as providing opportunities for employees to be able to provide ideas that will support the company's progress. PO-O does not mediate the effect of IHRMB on Job Satisfaction because IHRMB is a control tool for management and company owners to review overall company performance.